Compressive properties and microscopic analysis of engineered cementitious composites after salt freezing - Che, Jialing; Gong, Mengying; An, Xue; Liu, Haifeng; Doh, Shu Ing (Elsevier Ltd, 2022)
In order to study the compressive properties of Engineered Cementitious Composites (ECC) after salt freezing, the failure, compressive strength, and deformation capacity of cubic concrete specimens subjected to single-side freezing–thawing cycles considering the number of cycles, aggregate type Maowusu or Tengger Desert sands (MDS and TDS, respectively) and river sand (RS), and salt medium (NaCl or NaCl + Na2SO4). The results showed, In the presence of salt, the compression failure modes of all samples involved the formation of vertical cracks in the stress direction, but MDSECC and TDSECC showed better integrity than C30 concrete. With increasing freeze–thaw cycles, the strengths, slopes of the stress–strain curves, peak stress, and curve area of the desert sand specimens decreased, but the residual stress and ductility increased. Through regression analysis of the strength loss rate, the ECC lifetime was predicted, and using X-ray diffractometry and scanning electron microscopy, the effects of salt freezing on the mechanical properties of ECC were revealed.